Structure of the Arthropod Phytophagous Complex of Soybean in the Right-Bank Forest-Steppe of Ukraine - Pashkovskyi, V.A.; Babych, O.A. (Quarantine and plant protection, 2026)
Goal. To determine the ecological and functional structure of the complex of arthropod soybean pests in the Right-Bank Forest-Steppe of Ukraine, and to identify the species composition, as well as the dominant and associated groups, based on feeding habits and the nature of damage throughout the crop’s growing season. Methods. The research was conducted in 2023—2025 under field conditions in soybean agrocenoses. Depending on the species composition of phytophages, the following methods were used: route surveys of crops, sweep net sampling, visual assessment of pest abundance on plants, and soil excavation to detect concealed (soil-dwelling) forms. To analyze the community structure, ecological biodiversity indices (Shannon, Simpson, Pielou) were applied, along with comparative analysis of species abundance and frequency of occurrence were applied. Results. It was established that complex of arthropod phytophages on soybean has a clearly expressed functional structure and is represented by four main groups: soil-dwelling polyphagous pests, leaf-feeding, sucking, and generative pests, accounting for 20—23%, 33—38%, 20—23%, and 14—18%, respectively. Among them, the most economically significant species are Agriotes spp., Sitona spp., Helicoverpa armigera, and Etiella zinckenella. Analysis of biodiversity indices indicated a high level of species diversity (H´ = 2.96), relative evenness of species distribution (J´ = 0.94), and low dominance (D = 0.061), which characterizes the phytophagous community as polycomponent and stable. Conclusions. The complex of phytophagous arthropodes of soybean in the Right-Bank Forest-Steppe of Ukraine is polycomponent and relatively stable, with a predominance of leaf-feeding species. At the same time, generative and sucking phytophages determine the main level of potential harmfulness. High evenness and diversity of the community do not exclude the risk of local outbreaks of certain species under favorable agroclimatic conditions. The obtained results have practical significance for improving monitoring systems and integrated soybean protection.